Bound exciton engineering approach for tuning the thermal lensing phenomenon in anatase TiO2: Gd nanosystems - Oriparambil Sivaraman Nirmal Ghosh; Sethuraman Gayathri; Srinivasa Rao Allam; Alok Sharan; S.B. Sruthil Lal; Modigunta Jeevan Kumar Reddy; A.M. Shanmugharaj; Annamraju Kasi Viswanath (Chemical Physics Impact)
We report a comprehensive investigation of the third-order nonlinear interaction of femtosecond laser pulses with nanostructured anatase TiO2 doped with varying concentrations of gadolinium impurities. The samples were synthesized using a facile sol‒gel method. The physicochemical characteristics of the prepared samples were investigated using various analytical techniques, including XRD, SEM, TEM, SAED, UV‒Vis, PL and XPS. The average crystallite sizes of the pristine TiO2- and Gd (1, 2, and 3 %)-doped TiO2 nanoparticles were calculated to be 10.9, 9.2, 10.2 and 8.9 nm, respectively. The W-H plots also revealed average crystallite sizes in the range of 13.9, 16.6, 13.9 and 10.4 for pristine and Gd (1, 2, 3 %)-doped TiO2 nanoparticles. The lattice strain values for pristine and Gd (1, 2, and 3 %) doped TiO2 nanoparticles were computed as 0.00203, 0.00667, 0.0036 and 0.00262, respectively, from the W‒H plots. The average crystallite size was calculated to 9.2 nm from the TEM images using ImageJ software. The optical band gap values of pristine TiO2 and Gd (1, 2, and 3 %)-doped TiO2 nanoparticles were calculated to be 3.3, 3.23, 3.21 and 3.20 eV from the Kubelka–Munk function plot. The emission peaks of pristine and Gd(1,2,3 %) doped TiO2 nanoparticles were calculated as 3.2, 3.23, 3.26 and 3.32 eV from the photoluminescence spectra recorded at 330 nm photo excitation. The binding energies of the O1s, Ti2P and Gd4d peaks present in the survey scan of TiO2 nanoparticles doped with one weight percentage of Gd impurity were 528.79, 531.53, 457.53, 463.25 and 149.6 eV, respectively. The third-order nonlinear characteristics of the TiO2:Gd samples were probed using the ultrafast laser Z-scan technique. We observed that the density of bound excitons can be regulated by controlling the dopant concentration. The strong oscillatory interactions between photogenerated bound excitons, which act as dipole oscillators with large oscillating frequencies, were recorded using a single-beam femtosecond Z-scan. The third-order nonlinear susceptibility χ(3) for pristine and Gd(1,2,3 %)-doped TiO2 nanoparticles were calculated as 7.258 × 10-18, 9.4 × 10-18, 11 × 10-18 and 13 × 10-18 cm2/V2, respectively. The obtained results suggest that the thermal lensing phenomenon in nanostructured anatase TiO2 can be generated and effectively controlled using a band gap engineering technique. We determined that the small pump power in nonlinear media with controllable band fluctuations can produce large phase distortions in TiO2:Gd nanosystems. Our findings reveal that Gd doping induces controlled modification of the electronic structure of TiO2, leading to a tailored energy landscape for exciton formation and binding. These findings provide a novel approach for engineering systems of TiO2-based nanostructures for energy-efficient optical-limiting nanophotonic systems and optoelectronic-switching devices.